Analysis Of The Impact Of Digital Era Developments On The Needs For Frontliners In Indonesian Sharia Banks Branch Office of Padang Bulan - Dhea Ananda Saskia; Fauzi Arif Lubis; Tri Inda Fadhila Rahma (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the impact of digital banking transformation on the demand for frontliners at Bank Syariah Indonesia (BSI) KCP Padang Bulan using a mixed methods approach. Quantitatively, data were collected through questionnaires from 112 respondents and analyzed using descriptive statistics, Pearson correlation, and simple linear regression in SPSS 20.0. Qualitatively, a Systematic Literature Review (SLR) was conducted on relevant studies from 2018–2024 to identify trends and patterns in the shift of frontliner roles. The results show that digital banking significantly affects the demand for frontliners, with a coefficient of determination (R²) of 23.4% and a positive regression coefficient (B = 0.218). While digitalization reduces routine transactional tasks typically handled by frontliners, it simultaneously redefine their roles into more strategic, consultative, and digital-support functions. The findings indicate that frontliners are still needed, but with new competencies, especially in digital literacy and customer engagement. This implies that Islamic banking institutions must reorient their human resource strategies to sustain relevance in the digital era